Life Forms and Biological Spectrum of the Flora of Barnadi Wildlife Sanctuary, Assam, India - Talukdar, S. R.; Deori, Chaya (Indian Forester, 2015)
In the present study, 459 species of Angiosperms and Pteridophytes have been classified, based on collection and plant habit into different life forms and a biological spectrum of the flora of Barnadi Wildlife Sanctuary, Assam, India have been worked out and compared with Raunkiaer’s normal spectrum to ascertain the life form. The result revealed that the life forms of the sanctuary is disturbed due to growing anthropogenic disturbance and in the days to come a more serious efforts of conservation measures are required for the restoration of the floristic diversity of the sanctuary.